Mechanics-based fragility curves for Italian residential URM buildings - Donà, Marco; Carpanese, Pietro; Follador, Veronica; Sbrogiò, Luca; da Porto, Francesca (Bulletin of earthquake engineering, 2021)
Seismic risk assessment at the territorial level is now widely recognised as essential for countries with intense seismic activity, such as Italy. Academia is called to give its contribution in order to synergically deepen the knowledge about the various components of this risk, starting from the complex evaluation of vulnerability of the built heritage. In line with this, a mechanics-based seismic fragility model for Italian residential masonry buildings was developed and presented in this paper. This model is based on the classification of the building stock in macro-typologies, defined by age of construction and number of storeys, which being information available at national level, allow simulating damage scenarios and carrying out risk analyses on a territorial scale. The model is developed on the fragility of over 500 buildings, sampled according to national representativeness criteria and analysed through the Vulnus_4.0 software. The calculated fragility functions were extended on the basis of a reference model available in the literature, which provides generic fragilities for the EMS98 vulnerability classes, thus obtaining a fragility model defined on the five EMS98 damage states. Lastly, to assess the reliability of the proposed model, this was used to simulate damage scenarios due to the 2009 L’Aquila earthquake. Overall, the comparison between model results and observed damage showed a good fit, proving the model effectiveness.